PEMBINAAN SUMBERDAYA APARATUR DALAM RANGKA PENINGKATAN KINERJA PEGAWAI DI BAPPEDA KOTA SAMARINDA - Shinta Rizki Delvinda (Jurnal Paradigma (JP), 2017)
The aim of is article is to explain about the process of aparatus development of Bappeda Kota Smarinda. The result of study states that aparatus development of Bappeda Kota Samarinda in order to performance enhancement goes with an expectation. Aparatus development through Leadership and Functional Trainning has directly influence to performance enhancement of Bappeda Kota Samarinda.